Molecular dynamic simulation of plasma material interaction to calculate theoretical sputtering yield - Alper, P. (Karagandy University of the name of acad. E.A. Buketov, 2023)
In a fusion reaction two light nuclei, Deuterium and Tritium merge to form a single heavier nucleus Helium. However, two positive nuclei repel each other. In order to merge two nuclei they need to have very high velocities. High speed means, high temperature. For the reaction it is significant for a nuclei to keep at 100 million °C temperature. At this temperature D and T atoms form a plasma. In order the reaction to take place, the plasma temperature must be conserved or plasma should not be cooled. Tokamak reactors are designed to confine the plasma in a magnetic field. Thus, the cooling of the plasma is prevented by hitting the reactor walls. Plasma density and temperature must be at a certain level in order to initiate the reaction and to ensure continuity. During the reaction process, positive and negative ions escaping from the magnetic field environment interact with Tokamak walls and cause deformation. This causes the plasma wall to deteriorate over time and the release of neutrons to the environment. Plasma-Wall interaction is one of the most important problems that cause interruption of fusion in Tokamak rectors. The materials which most resistant to ion corrosion in the plasma wall are graphite, beryllium, aluminium and tungsten. In this work, plasma-material interaction is studied theoretically physical and chemical erosion caused by the plasma interactions of different wall material samples (graphite, aluminium and Tungsten) used in the fusion reactor and investigated with the Monte Carlo method with molecular dynamics.
Keywords: Plasma; Nuclear Fusion; Molecular Dynamics; Sputtering Yield; Monte Carlo